Triptans other than sumatriptan in child and adolescent migraine: literature review. (March 2011) - Vollono, Catello; Vigevano, Federico; Tarantino, Samuela; Valeriani, Massimiliano
Abortive drugs used for migraine in children and adolescents are usually the same as those used in adults. Only a few studies have assessed the efficacy of triptans other than sumatriptan in pediatric migraine. This systematic review describes the evidence concerning the efficacy and tolerability of these triptans. The PubMed research produced 481 results and only seven studies were randomized controlled trials. A total of 11 articles were reviewed. Zolmitriptan and rizatriptan were superior to placebo in most studies. Almotriptan demonstrated a high profile of tolerability. A single study of eletriptan demonstrated no statistical difference between this drug and placebo in terms of both efficacy and tolerability. All studies have reported a good triptan safety profile. The conflicting data regarding triptan efficacy are probably due to differences in populations, methodologies and efficacy measures among the different studies. Triptans are an important option in the symptomatic treatment of childhood and adolescent migraine.